War and Peace in Modern India - Raghavan, S. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
A study of Indian foreign policy under Jawaharlal Nehru, concentrating on the fundamental questions of war and peace. Looks at Nehru's handling of the disputes over the fate of Junagadh, Hyderabad and Kashmir in 1947-48; the refugee crisis in East and West Bengal in 1950; the Kashmir crisis in 1951; and the boundary dispute with China 1949-62.